The Use of Zebrafish's Flexibility in the Regeneration of Their Hearts After Injury in Human - Ashref, Lujain (Libyan international medical university basic medical science, 2020)
Myocardial infarction had been an ongoing concern to the medical world as the mortality rates are increasing day by day. An animal having more than 70% of their genes in common with humans as well as the same major organs and tissues caught the attention of scientists because of its extraordinary ability to regenerate their heart after damage, the study revolved around the detailed mechanism of the zebrafish’s heart regeneration by a set of experiments. The results were promising as the zebrafish’s heart managed to fully recover in terms of their anatomical, histological and physiological makeup when they had been injured. This was further on studied to come up with therapeutic agents that could lead to the same regenerative process in human hearts after cardiac failure.
The heart, like any other organ in the body is in need of constant supply of oxygen and nutrients to keep up with the body’s needs, and this is mediated via the coronary arteries, they’re two in number and only function to deliver oxygenated blood to the heart. One of the leading causes of death in the world, constituting 30% is myocardial infarction (MI), it happens due to blockage to one of the coronary arteries that results in cardiac ischemia and death of about 25% of cardiomyocytes